Simultaneous determination of azathioprine and its metabolite 6-mercaptopurine in human plasma using solid phase extraction-evaporation and liquid chromatographypositive electrospray tandem mass spectrometry - Raja, Mokkaisamy Jegadeesh; Kavitha, Jegadeesh Raja; Kumar, Kothamasu Pavan; Sivakumar, Thangavel (International Current Pharmaceutical Journal, 2012)
A simple, rapid, specific, sensitive and liquid chromatography coupled with tandem mass spectrophotometric method was developed and validated for the estimation of azathioprine and its metabolite 6-mercaptopurine in human plasma by using lamivudine and 6-mercaptopurine D3 as the internal standard. Azathioprine and 6-mercaptopurine were extracted from human plasma by solid-phase extraction (SPE)-Evaporation method, using Oasis MCX cartridge for cleaning procedure. The stationary phase was chromatographed on a ZORBAX SB CN, (75X50 mm, 5 µ) column where as mobile phase constitutes of acetonitrile: 2mM ammonium acetate (70:30 v/v) at a flow rate of 0.800 ml/min. The detection was performed with an Applied Biosystems Sciex API 4000 mass spectrometer by multiple reaction monitoring (MRM). The method validation proofs were carried out as per the USFDA guidelines as described, showing a linearity system (r2 > 0.99) over a range of 2.455 ng/mL to 106.568 ng/mL for azathioprine and 1.165 ng/mL to 101.143 ng/mL concentrations for 6-mercaptopurine and a recovery shows 99.36% and 100.44% for azathioprine and 6-mercaptopurine respectively. The results show that this proposed approach is effective and can be applied to the extraction and analysis of other pharmaceutical compounds. DOI: http://dx.doi.org/10.3329/icpj.v1i11.12059 International Current Pharmaceutical Journal 2012, 1(11): 342-352